Actualization Of Human Rights In The Case Of Rempang Island In Indonesia In The Perspective Of Environmental Law - Aisha Nur Habiba; Annisa Ayu Melati; Nur Hamda Sa'idah; Wike Vimayanti (JURNAL HUKUM SEHASEN, 2023)
This study aims to further review human actualization in the case of Rempang Island in Indonesia in the perspective of environmental law. This study investigates the case of Rempang Island in Indonesia, a conflict containing human rights violations reviewed through environmental law. In the perspective of environmental law, a healthy environment is everyone's right without exception, so environmental damage is against the law. Violations in the environmental domain must be safeguarded based on appropriate legal settlement procedures. In the case of Rempang Island, the actualization of human rights in the perspective of environmental law can be interpreted as the protection of people's rights to their land and environment, as well as transparent and effective law enforcement to prevent environmental damage and human rights violations.